A New Overgrowth Syndrome is due to Mutations in RNF125. Issue 12 (December 2014) - Tenorio, Jair; Mansilla, Alicia; Valencia, María; Martínez‐Glez, Víctor; Romanelli, Valeria; Arias, Pedro; Castrejón, Nerea; Poletta, Fernando; Guillén‐Navarro, Encarna; Gordo, Gema; Mansilla, Elena; García‐Santiago, Fé; et al.
<x xml:space="preserve">Abstract</x> We have identified four mutations in a novel overgrowth gene, RNF125 (Fig A), in six patients with overgrowth, macrocephaly, intellectual disability, mild hydrocephaly, hypoglycaemia and inflammatory diseases resembling Sjögren syndrome. RNF125 encodes an E3 ubiquitin ligase. Functional characterisation showed that the mutations resulted in a dysregulation of RNF125 mRNA expression (Fig B). Additionally, clear differences in induction and degradation kinetics of RIG‐I, a RNF125 target protein, between patients and control fibroblasts were observed (Fig C‐E). <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>